Enhancing Financial Resilience of Women Entrepreneurs through Strengthened Digital Financial Literacy - Sari, Ratna Candra; Zuhrohtun, Zuhrohtun; Pranesti, Arin; Yudhiyati, Ratna; Udhma, Umi Syafaatul; Nurbaiti, Novita (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
This study investigates the impact of digital financial literacy (DFL) on the financial resilience of women entrepreneurs. The research adopts an explanatory approach, drawing on data from 208 women entrepreneurs based in Yogyakarta and Central Java, Indonesia. To test the proposed hypotheses, partial least squares structural equation modeling (PLS-SEM) was employed. The findings indicate that DFL significantly influences financial behavior, with these effects extending to future financial decisions. Enhancing DFL among women entrepreneurs positively affects their financial behavior, ultimately contributing to greater financial resilience. A key contribution of this research lies in its focus on women entrepreneurs, a demographic often overlooked in studies on financial literacy. Additionally, the study distinguishes between spending and saving behaviors by separating current financial actions from those intended for the future. This distinction enables a more nuanced analysis of how different financial behaviors, facilitated by digital financial technologies, affect financial resilience. Keywords: digital financial literacy, financial resilience, woman entrepreneur